Treatment outcomes of conventional or high-dose ranibizumab for vascularized pigment epithelial detachment based on lesion subtypes - Chan, Clement K; Sarraf, David; Abraham, Prema (European journal of ophthalmology, 2018)
A post hoc study was conducted to compare visual and anatomic outcomes of vascularized serous pigment epithelial detachment (Group 1) with fibrovascular pigment epithelial detachment (Group 2) due to age-related macular degeneration treated with either 0.5 or 2.0 mg ranibizumab injections. A prospective, randomized trial was performed with the following regimens for 12 months: (1) 0.5 mg monthly, (2) 0.5 mg monthly for 4 months followed by pro re nata injections, (3) 2.0 mg monthly, and (4) 2.0 mg monthly for 4 months followed by pro re nata injections. Primary measure was best-corrected standardized vision. Secondary measures included central subfield, thickness surface area A , greatest linear diameter, heights of pigment epithelial detachment and choroidal neovascularization (CNV), subretinal fluid, cystoid macular edema, and adverse events. For 36 eyes (8 in Group 1 and 28 in Group 2), follow-up time was 12 months. There were no differences in baseline features between groups except for pigment epithelial detachment A (Group 2 > Group 1). Two-way analysis of variance showed comparable improvements in anatomic and vision outcomes. Three-way analysis of variance also showed similar responses for both lesion subtypes with high-dose treatment. There was a trend toward greater pigment epithelial detachment resolution in Group 1 eyes. There were no differences in retinochoroidal angiomatous proliferation (Type-3 CNV) and cataracts between groups, although greater percentages of eyes in Group 1 developed retinal pigment epithelial tears (25% vs 10.7%). There were no differences in vision and anatomic outcomes between lesion subtypes, and similarly, more rapid responses to high-dose than conventional-dose ranibizumab occurred for eyes with both lesion subtypes. More retinal pigment epithelial tears may develop in eyes with vascularized serous pigment epithelial detachment.